The Growing Public Domain in Medicine - Vishnubhakat, Saurabh (Science and Technology Law Review, 2014)
This Article describes the growing public domain of inventions associated with drugs and medicine, and geographies associated with identifiable shifts in the balance of innovation that may be especially favorable for promoting wider access to socially useful technologies. To do so, it departs from the largely ex ante perspective that currently informs the intersectional debate regarding human rights and patent rights and, instead, looks backward to inquire what innovations from past patents have already become publicly available in service of the human rights objective of greater access to technology. Ex post analysis of this kind may help public and private institutions alike in identifying cycles of innovation that sustainably deprioritize socially valuable technologies and leave them free for public use.